A storm event watershed model for surface runoff based on 2D fully dynamic wave equations. Issue 4 (20th March 2012) - Costabile, Pierfranco; Costanzo, Carmelina; Macchione, Francesco
Abstract The main purpose of this work concerns the development and testing of an overland flow model based on the two‐dimensional fully dynamic shallow water equations. Three key aspects, fundamental to get accurate, efficient and robust computation of surface runoff at basin scale, are discussed by transferring the main findings obtained by the recent research on the topic of dam‐break wave and flood propagation in the context of rainfall–runoff modelling. In particular, attention is focused on the numerical flux and bottom slope source terms computation, on a numerical treatment of friction slope terms and on an algorithm for dealing with wetting/drying fronts. The performances of the numerical model have been preliminarily evaluated using experimental or ideal tests characterized by very critical conditions for the stability of a numerical model. Then, attention was focused on a real event occurred in a sub‐basin of Reno river in Italy to analyse the suitability of the model in simulating real flood situations. The numerical results highlight the good performances of the model in all the simulations discussed in the paper. Copyright © 2012 John Wiley & Sons, Ltd.